2013
DOI: 10.1007/s13139-013-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Role of Dual-Time-Point 18F-FDG PET/CT in Differential Diagnosis of the Thyroid Incidentaloma

Abstract: Thyroid incidentalomas are common findings during imaging studies including 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) for cancer evaluation. Although the overall incidence of incidental thyroid uptake detected on PET imaging is low, clinical attention should be warranted owing to the high incidence of harboring primary thyroid malignancy. We retrospectively reviewed 2,368 dual-time-point 18F-FDG PET/CT cases that were undertaken for cancer evaluation from Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
1
18
1
1
Order By: Relevance
“…We performed ROC analysis to determine an optimal cut-off value. Here, we found that the AUC, specificities, and sensitivities for lesion SUVmax, ratio 1TLTBG, ratio 1TLBP, and ratio 1TLL, were significantly higher than the literature values (14, 18, 20). The 1TLTBG ratio performed best and yielded a sensitivity and specificity of 0.88 and 0.74, respectively.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We performed ROC analysis to determine an optimal cut-off value. Here, we found that the AUC, specificities, and sensitivities for lesion SUVmax, ratio 1TLTBG, ratio 1TLBP, and ratio 1TLL, were significantly higher than the literature values (14, 18, 20). The 1TLTBG ratio performed best and yielded a sensitivity and specificity of 0.88 and 0.74, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The AUC was 0.82 (Table 4). Others have attempted but failed to derive SUVmax thresholds that discriminate benign from malignant lesions (14, 17, 18, 20). Many groups solely focused on differentiating benign and malignant thyroid lesions based on SUVmax.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this, the Hounsfield unit ratio of thyroid nodules was assessed compared to the contralateral thyroid lobe on non-contrast CT to stratify further risk of malignancy in thyroid incidentalomas detected in 18 F-FDG PET/CT ( 27 ). Dual-time-point 18 F-FDG PET/CT and retention index were used in differential diagnosis of thyroid incidentaloma ( 28 ). Barrio et al ( 29 ) measured SUVmax, thyroid to background thyroid lesion SUVmax/thyroid background SUVmean (TL/TBG), thyroid to blood pool TL/blood pool SUVmean (BP), and thyroid to liver TL/liver SUVmean (L) ratios in benign and malignant lesions to test if intense focal 18 F-FDG thyroid uptake is associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the FDG PET image at a single time-point lacks the dynamic information regarding the FDG uptake in a lesion, and there is sometimes overlap of the standardized uptake value (SUV), that is, the semiquantitative measurement of FDG uptake, between benign and malignant tumors. The retention index (RI) of the lesion, which is defined as the percentage change in maximal SUV (SUVmax) between initial and delayed phase images, has been found to have clinical potential to predict malignance [ 12 , 13 ] and patient prognosis. [ 14 , 15 ] Another parameter derived from dual-phase FDG PET is the increment in SUVmax (SUVinc) of the tumor between initial and delayed phase image.…”
Section: Introductionmentioning
confidence: 99%